2016
DOI: 10.1093/aob/mcw162
|View full text |Cite
|
Sign up to set email alerts
|

Two tropical conifers show strong growth and water-use efficiency responses to altered CO2concentration

Abstract: Background and Aims Conifers dominated wet lowland tropical forests 100 million years ago (MYA). With a few exceptions in the Podocarpaceae and Araucariaceae, conifers are now absent from this biome. This shift to angiosperm dominance also coincided with a large decline in atmospheric CO 2 concentration (c a ). We compared growth and physiological performance of two lowland tropical angiosperms and conifers at c a levels representing pre-industrial (280 ppm), ambient (400 ppm) and Eocene (800 ppm) conditions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…In addition, it was recently suggested that Podocarpus guatemalensis (Podocarpaceae), a conifer species in Panama, could have a different strategy for soil N acquisition compared with broadleaf species (Dalling et al. ). Therefore, we hypothesized that podocarps associated with AMF are better at nutrient uptake than EM tree species in our study site and this hypothesis is consistent with the fact that podocarps (and other conifer species) are more abundant on N‐limited soils than on fertile soils in Borneo (Kitayama et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was recently suggested that Podocarpus guatemalensis (Podocarpaceae), a conifer species in Panama, could have a different strategy for soil N acquisition compared with broadleaf species (Dalling et al. ). Therefore, we hypothesized that podocarps associated with AMF are better at nutrient uptake than EM tree species in our study site and this hypothesis is consistent with the fact that podocarps (and other conifer species) are more abundant on N‐limited soils than on fertile soils in Borneo (Kitayama et al.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Dalling et al . ). The increase in A / g s caused by rising CO 2 is expected to partly mitigate increasing drought stress caused by global warming in coming decades (Roderick et al .…”
Section: Gas Exchange and Water‐use Efficiency In Response To Global mentioning
confidence: 99%
“…The role of the atmospheric carbon dioxide concentration ( p CO 2 ) drop over the EOT ( 55 , 56 ) appears less important than temperature. Tropical conifers are more responsive to atmospheric p CO 2 than tropical angiosperms, showing improved growth and water use efficiency under higher CO 2 ( 57 ). Despite this, conifers have demonstrated range expansions during cooler periods with lower atmospheric p CO 2 ( 57 ), as is observed in Central Asia ( Fig.…”
Section: From Eocene Shrub Dominance To Oligocene Collapse (Phase 1)mentioning
confidence: 99%
“…This represented a catastrophic shift to a new environmental state, previously recognized in the sedimentological record as a change from a “wet” desert with ephemeral saline lakes and mudflats within the basins, to a more arid desert with no lakes in many parts of Central Asia ( 16 , 64 , 77 , 78 ). A drop in atmospheric p CO 2 would have decreased water use efficiency, thus enhancing the effect of increased aridity ( 57 ). An atmospheric p CO 2 drop could also have played an important role in differential survival of Asian plant species over the EOT, which requires further investigation.…”
Section: A Regime Shift At the Greenhouse To Icehouse Transitionmentioning
confidence: 99%